Assessment of haemoglobin level in patients with recurrent oral ulcer of a sample of Malaysian population - Mustafa Al-Ahmad, Basma Ezzat; Kashmoola, Muhannad Ali; Mustafa, Nazih Shaban; Al-Ani, Imad Matloub Dally (Research & Reviews, 2015)
Recurrent oral ulcers are common painful oral mucosal conditions seen among patients which generally last a few days and typically affect the tongue, lips,cheeks, and can appear in any part of the mouth. The purpose of this study was to investigate the relationship between Haemoglobin [Hb] statuses with recurrent oral ulceration [ROU] by measuring the Hb level. Forty seven adult Malaysian patients attending the oral medicine clinic, IIUM, were examined for ROU and its relation with Hb level using haemoglobinometer. Both minor and major ulcers were observed in the patients attending oral medicine clinic of Kulliyyah of Dentistry. The male and female patients with ROU had significantly low haemoglobin level with P<0.001. In conclusion, the present study shows high relationship between recurrent oral ulceration and haemoglobin level.